A status report on glanders in Madhya Pradesh, India: a re-emerging zoonotic disease - Bijlwan, Aanchal; Kumar, Saurav; Kaurav, Yogesh S.; Sinha, Veena; Singh, Shailendra (International Journal Of Community Medicine And Public Health, 2023)
Glanders, a zoonotic disease caused by Burkholderia mallei, has resurfaced as a significant health concern in Madhya Pradesh, India. This status report aims to provide a comprehensive overview of the current status of glanders, exploring its epidemiology, clinical implications, and socio-economic impact in the region. The data was collected in the state of Madhya Pradesh comprising of seven divisions and 52 districts with a population of 8.74 crores (projected data from census 2011). The data available in Interated Disease Surveillance Program (IDSP) cell of Directorate Health Services (Madhya Pradesh) was collected from the year 2017-2021. 17 positive cases were reported in six districts in the year 2018, and 11 cases were reported in six districts in the year 2019. Subsequently, in the year 2020, a total of 3 cases were reported from a single district, and 4 cases were reported from 4 districts in the year 2021. Early detection of disease in susceptible animals, strict quarantine measures, testing and safe destruction of infected carcasses, adequate compensation to animal owners, disinfection of infected premises, and public awareness of glanders and their zoonotic implications through veterinary extension services can be some of the effective countermeasures against glanders.